Etiology and Clinical Features of Diplopia in South China: Analysis of 303 Cases - Wang, Zhonghao; Zhu, Binbin; Fu, Licheng; Yan, Jianhua (Frontiers in Neurology, 2022)
Purpose: To provide a new classification system for diplopia and evaluate the etiology and clinical features of diplopia subtypes in south China. Methods: In this retrospective study, all patients presenting with diplopia over the period from 2012 to 2014 in south China were reviewed. Patients were categorized into 3 groups according to their extraocular muscle (EOM) dysfunction: single EOM (sEOM), multiple EOMs (mEOMs) and a comitant strabismus group. Clinical data evaluated included age, sex, medical history, etiology and duration of diplopia, ocular alignment and ocular motility. Results: A total of 303 patients were enrolled. The most common type of EOM dysfunction was sEOM (158 cases, 52.1%), followed by mEOMs (n=119, 39.3%) and finally the comitant strabismus group (n=26, 8.6%). Overall, the most common cause of diplopia involved orbital diseases. Within the sEOM group, microangiopathy (n=31, 19.6%) and trauma (n=32, 20.3%) were the major etiologies, with the lateral rectus (n=86, 54.4%) being the most frequently involved. There were 12 (4%) patients with nasopharyngeal carcinoma (NPC). Thyroid associated ophthalmopathy (TAO - 56 cases, 47.1%) was the predominant etiology found in the mEOMs group. Acute acquired comitant esotropia (AACE -14 cases, 53.9%) was the most common etiology in the comitant strabismus group. Conclusions: This new classification system for assessing diplopia as based on EOM dysfunction represents an easy-to-follow approach that can be readily adapted for clinical use. While microangiopathy and trauma represent common etiologies of diplopia, both orbital diseases and NPC also warrant special attention when assessing diplopia within patients in south China.